2019
DOI: 10.1111/inm.12609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental mental illness on children's HoNOSCA results in a regional child and adolescent mental health service

Abstract: Use of routine outcome measures are frequently used to ascertain improvement in children's symptomology, this study examined whether living with a parent with a mental illness impacted outcome measures. The study examined 134 children attending a Child and Adolescent Mental Health Service (CAMHS). The majority lived with a parent reporting mental illness. Routine HoNOSCA and CGAS outcome measures were collected over a 6‐month period. Children of parents with a mental illness scored higher on most outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…Almroth, M et al analyzed the relationship between parental expectations and child harmony by investigating whether parental academic expectations are congruent with children's expectations and exploring, in the family, the predictors of children's mental health [10]. Naughton, M. F. A et al demonstrated that children's mental health is in part related to parental mental status as well as parenting styles by examining the mental health of a number of children and adolescents and collecting routine HONOSCA and cGAS outcome indicators [11]. Sanmarchi, F et al concluded that sedentary behavior is associated with poorer health outcomes and that parenting behaviors can influence children's lifestyle and mental health status to some extent [12].…”
Section: Introductionmentioning
confidence: 99%
“…Almroth, M et al analyzed the relationship between parental expectations and child harmony by investigating whether parental academic expectations are congruent with children's expectations and exploring, in the family, the predictors of children's mental health [10]. Naughton, M. F. A et al demonstrated that children's mental health is in part related to parental mental status as well as parenting styles by examining the mental health of a number of children and adolescents and collecting routine HONOSCA and cGAS outcome indicators [11]. Sanmarchi, F et al concluded that sedentary behavior is associated with poorer health outcomes and that parenting behaviors can influence children's lifestyle and mental health status to some extent [12].…”
Section: Introductionmentioning
confidence: 99%